Ecological Fall, Resilience and Stability: Unravelling Eco-theological Didacticism in Karen Tei Yamashita’s Through the Arc of the Rain Forest - Hanif, Zahra (Journal of Research in Humanities, 2023)
The aim of this research paper is to explore the subcategory of environmental humanities i.e. eco-theology and argue that the conjunction of environmental humanities and the didactic nature of theology can prove fundamental in raising awareness about environmental degradation resulting from the anthropocentric approaches towards nature and can possibly lead to more environmentally sustainable behaviors. The objective of this research paper is to examine Asian American writer Karen Tei Yamashita’s novel Through the Arc of the Rain Forest for its eco-theological underpinnings. The researcher intends to analyze the plot structure of the novel to highlight how the Christian narrative of the Fall is reflected in the unfolding of the plot and in the symbolic presentation of the forbidden fruit and serpent in the form of the Matacao and American entrepreneur J.B. Tweep respectively. The chapters of the novel have been divided into six parts initiating the narrative with “The Beginning” that leads to “More Development” and “Loss of Innocence” revealing the exploitative relation of the characters to the Brazilian Amazon, which is fictionalized as an area called the Matacao. The plot structure reiterates the Edenic bliss of Adam and his ultimate loss of innocence which is reflected in the modern day loss of innocence at the hands of excessive technological advancements destroying the environment. Yamashita uses the last part “Return” as a silver lining emulating the didactics of religion which promise rewards after stating the severe punishments resulting from morally questionable deeds. “Return” normalizes the doomsday-like environmental havoc unleashed by Matacao eating bacteria. The earth resets its natural functioning with characters taking a recourse to an Eden-like place reflecting earth’s resilience and inherent stability in ways that resonate with Canadian ecologist Holling’s theory of ecological resilience and stability.